Maritime Security in the Indo-Pacific: The Role of the US and its Allies. (2nd January 2017) - Gopal, Prakash
ABSTRACT: The strategic construct of the Indo-Pacific has today gained salience due to the region becoming the centre of gravity of economic development and social mobility. This has been driven, to a large extent, by commercial maritime activity and the assurance of security on the global commons. The US has played a significant role in the provision of this security, with Japan and Australia emerging as vital regional partners in this effort. While the US' presence in the region was primarily motivated by its Cold War aim of containing communism, the post-Cold War period has demanded a fresh approach to maritime security in the Indo-Pacific. Transforming geo-political and strategic considerations have, however, raised questions on the continued efficacy of this system. With the somewhat problematic rise of China, the US, Japan, Australia and India, as major regional maritime powers, need to evolve a regional maritime security architecture that will continue to support the peaceful and legitimate use of the seas.